Analysis of Higher Order Thinking Skills in Exponents And Logarithms - Khadijah, Khadijah; Amrin, Irfan Pratama; Muh. Zainal Pratama (PT ARRUS Intelektual Indonesia, 2025)
This study is intended to investigate the subject of exponent, roots and logarithms and how teacher can help students understand this subject better. The study method displays several facts about Exponent, Roots and Logarithm, and the correlation of them in daily life. Then, in every part, it will derive and prove the Properties of Exponent, Roots and Logarithm. Analyzing the impact of lack of concept understanding on students' ability to solve mathematics problems. Identifying common errors in learning exponent, root, and logarithm forms material. Propose strategies and ways to avoid them. Presenting effective learning media for exponent, roots and logarithm. And outlining the benefits of using UN type questions in improving understanding and Higher Order Thinking Skills (HOTS). The result of this study, we found that the Exponent, Roots and Logarithm are important foundation for various applications in daily life and in higher mathematics subjects. To assist learners in learning this material, the paper also presents a range of suggested learning media. These include the use of manipulatives, interactive whiteboards, learning videos, and worksheets. These media will help learners to visualize the concepts and apply them in different contexts. Finally, the paper suggests using UN-type questions (HOTS) to test learners' understanding. These problems are designed to encourage learners to think at a higher level in mathematical problem solving, so that they can better master the concepts of exponents, roots and logarithms.